PRINSIP-PRINSIP TRANSFORMASI KEBIJAKAN PEMBANGUNAN BERKELANJUTAN DAN PENGENDALIAN PERUBAHAN IKLIM BERDASARKAN PARADIGMA SYSTEMS THINKING - Karuniasa, Mahawan (Fakultas Kehutanan Universitas Lancang Kuning, 2019)
The global development using economic has resulted social and environmental issues, including climate change. After the Silent Spring and Brundtland Report publicated, global development paradigm has changed, from economic to sustainable development. National development continues to support the growing population for moving forward into developed country. Nevertheless, the national development undertaken showed an unsustainable development pattern. This research aimed to obtain the principles of transformation sustainable development and climate change policy in Indonesia used Soft System Methodology. Reflections on sustainable development and climate change countermeasure showed that national development was economic-oriented and left environmental quality, green house gas pattern has been moving toward business-as-usual conditions. The principles of policy transformation to realize the sustainable development and climate change countermeasure in Indonesia, the paradigm, from static to a dynamic and holistic of Systems Thinking paradigm, especially for stakeholders and decision makers. It necessary to build awareness and operational actions of stakeholders, including the government institutions, that Law Nomor 32 Year 2009 on Environmental Protection and Management context of sustainable development to achieve sustainable Indonesia. To face global issues, such as climate change and sustainable development goals, need to constructed according to economic, social and environmental conditions.